Strategi Media Sosial Terhadap Peningkatan Pemasaran Pada Usaha Jahit Ferra Fashion House - Ferra Fajriyah; Fitriani Fitriani; Miftah Fadhli Asad; Sri Aisyah Yope (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to assess the impact of social media use on the growth of Ferra Fashion House's business. This business uses digital platforms like Instagram and WhatsApp to display product results and facilitate long-term communication with customers. The methodology used in this study is a kualitatif deskriptif approach with a focus on literature studies. The study's findings indicate that social media has a significant impact on increasing visibility, market share, and customer satisfaction. More than 70% of new transactions originate from initial interactions through social media, which were not previously facilitated by traditional promotions. Even though there are issues with content consistency and keterbatasan in digital marketing strategies, social media is still an effective tool for strengthening business-customer relationships and increasing business day-to-day in the digital age